INTEGRATING EXPERIENTIAL AND SOCIAL MEDIA MARKETING IN HIGHER EDUCATION: DETERMINANTS OF UNIVERSITY CHOICE AMONG INDONESIAN STUDENTS - Dwi Andayani Vita setyawardani; Yuli Kartika Dewi (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2025)
This study aims to examine how experiential marketing and social media marketing jointly influence students’ university decisions within Indonesia’s increasingly competitive private higher education sector. Private universities face persistent challenges in attracting prospective students as traditional promotional approaches have become less effective among digitally oriented youth. This creates an urgent need to understand how emotionally engaging experiences and authentic digital interactions shape enrollment decisions. Although prior studies have examined these variables separately, limited research integrates them within a single explanatory framework capable of capturing their synergistic effect. Using a quantitative survey design, data were collected from 150 students who had engaged with both campus experiences and social media promotions. A structured Likert-scale questionnaire measured three constructs, and reliability, validity, and multiple regression analyses were performed using JASP. The results show that experiential marketing and social media marketing significantly influence university decision-making, with social media marketing exerting a slightly stronger effect.